Binder pitch for carbon material production and method for producing carbon material

By using characteristic asphalt (softening point 70°C to 120°C, fixed carbon amount or more, quinoline insoluble components or less, initial distillation point or more, Carson yield value or more, Carson yield value or more) as the binder, the problem of low carbon density is solved, and the manufacturing of high-density carbon materials and high carbonization rate are achieved while maintaining good kneading properties.

CN119790110APending Publication Date: 2025-04-08RESONAC CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480002387.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-07
Filing Date
2024-04-23
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

It is difficult for the prior art to achieve good kneading and high carbonization rate of carbon materials such as graphite electrodes at the same time, resulting in low carbon density, and it is necessary to impregnate asphalt and re-fired to reduce porosity.

Method used

Asphalt with a softening point of 70°C to 120°C, a fixed carbon amount of 50.0 mass % or more, a quinoline insoluble component of 18.0 mass % or less, a Carson yield value of 0.18 Pa or more at a softening point of 100°C was used as the binder, and the rheological characteristics of the bitumen were adjusted to suppress the loss of the binder bitumen during firing.

Benefits of technology

The manufacturing of high-density carbon materials is achieved, the carbonization rate and density are improved, while the good kneading properties are maintained, and the number of impregnated bitumen and refiring is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790110A_ABST
    Figure CN119790110A_ABST
Patent Text Reader

Abstract

In this method for producing a carbon material, an asphalt having a softening point of 70-120 DEG C, a fixed carbon content of 50.0 mass% or more, a quinoline insoluble content of 18.0 mass% or less, an initial boiling point of 320 DEG C or more, and a Casson yield value at softening point + 100 DEG C of 0.18 Pa or more is used as a binder asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing a carbon material such as a graphite electrode and a binder pitch. Background Art

[0002] Carbon materials such as graphite electrodes used in electric furnaces for remelting iron can be manufactured as follows: Aggregates such as coke and asphalt (referred to as "binder pitch") are kneaded / molded at a temperature above the softening point of the binder pitch, then fired and graphitized. Carbon materials require properties such as high mechanical strength, high electrical conductivity and high thermal conductivity, so high density is preferred. However, during the firing process, the fired body becomes a structure with many pores due to the volatilization of low molecular weight components in the binder pitch. Therefore, the porosity is reduced by impregnating the fired body with asphalt (referred to as "impregnated pitch") several times and re-firing during the manufacturing process, so that the resulting carbon material has a high density.

[0003] The carbonization yield of the binder pitch in the molded body during the firing process is called the carbonization rate. The higher the carbonization rate, the higher the density of the resulting fired body, and thus the number of subsequent impregnations and re-firings of the impregnated pitch can be reduced, so it is preferred. Generally, there is a tendency that the higher the fixed carbon content of the pitch, the higher the carbonization rate, and therefore it is preferred to use such pitch as the binder pitch.

[0004] As a method for increasing the fixed carbon content of binder pitch, there is a known method of removing light components in the pitch by distillation, etc., but at the same time, the softening point also increases. Generally, when mixing aggregates such as coke and binder pitch, it is considered that a temperature of about 50°C higher than the softening point is required. Therefore, if the softening point is high, there is a problem of increased load on the equipment.

[0005] In order to solve this problem, there is a method of adding a diluent oil to a pitch having a high fixed carbon content and a high softening point (Patent Document 1).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: U.S. Patent No. 6352637 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the method described in Patent Document 1, it is necessary to add a diluent oil with a lower boiling point, so there is a problem of lowering the initial boiling point of the obtained asphalt. If the initial boiling point is too low, the amount of light components that volatilize during kneading is large, thereby causing an increase in viscosity during kneading, and there is a problem of reduced kneading properties. As mentioned above, it is difficult to achieve good kneading properties and a high carbonization rate at the same time only from the perspective of the fixed carbon content and softening point that have been particularly valued before. In the present disclosure, a binder asphalt that can achieve good kneading properties and a high carbonization rate at the same time and a method for producing a high-density carbon material using the binder asphalt are provided.

[0011] Means for solving problems

[0012] When the molded body is fired, the softening and viscosity reduction of the binder asphalt in the molded body occur while the temperature rises. At this time, if the loss of the binder asphalt from the molded body occurs, the carbonization rate decreases. In order to suppress the loss of the binder asphalt during such firing, it is believed that it is effective to use an asphalt that can maintain a higher viscosity during firing. However, such an asphalt usually has a high softening point, so there is a problem of reduced kneading properties. The inventors of the present application believe that in order to suppress the loss of the binder asphalt during firing without reducing the kneading properties, the binder asphalt with the following characteristics is preferred: the viscosity is easily reduced in a state where the binder asphalt flows to a certain extent as in kneading, and the high viscosity is maintained in a state where the binder asphalt hardly flows as in firing. Based on this investigation, the inventors of the present application have repeatedly conducted in-depth research on the new perspective of combining the rheological properties of the binder asphalt in addition to the previously valued properties such as the fixed carbon content and softening point of the binder asphalt. It was found that when an asphalt with a higher Casson yield value is used as the binder asphalt even if the fixed carbon content is the same, a higher carbonization rate can be obtained, and a higher density carbon material can be obtained, thereby completing the present invention.

[0013] That is, the contents of the present disclosure relate to the following [1] to [4]. [1]

[0015] A binder pitch for carbon material manufacturing, having a softening point of 70°C to 120°C, a fixed carbon content of 50.0% by mass or more, a quinoline insoluble component of 18.0% by mass or less, an initial distillation point of 320°C or more, and a Casson yield value of 0.18 Pa or more at a softening point of +100°C. [2]

[0017] According to the binder pitch for producing a carbon material described in [1], the carbon material is a graphite electrode. [3]

[0019] A method for manufacturing a carbon material, wherein as a binder pitch, a pitch having a softening point of 70°C to 120°C, a fixed carbon content of 50.0% by mass or more, a quinoline insoluble component of 18.0% by mass or less, an initial distillation point of 320°C or more, and a Casson yield value of 0.18 Pa or more at a softening point of +100°C is used. [4]

[0021] According to the method for producing a carbon material described in [3], the carbon material is a graphite electrode.

[0022] Effects of the Invention

[0023] According to the present disclosure, a binder pitch that can achieve both good kneading properties and a high carbonization rate can be obtained. According to the present disclosure, a high-density carbon material can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] [ Figure 1 ] is a flow chart showing the petrochemical process of thermal decomposition of naphtha, etc. and the production process of ethylene tar.

[0025] [ Figure 2 ] is a graph showing the change over time in the rate of increase in viscosity of various pastes (mixtures of needle coke and various binder pitches, needle coke:binder pitch=3:7 (mass ratio)) at 170°C.

[0026] [ Figure 3 ] is a graph showing the change in viscosity when the shear rate at the softening point of the binder asphalt of Example 1 + 100°C (193°C) is changed.

[0027] [ Figure 4 ] is the Casson curve of the binder asphalt of Example 1 (measurement temperature: 193°C). DETAILED DESCRIPTION

[0028] Hereinafter, preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments, and it should be understood that various applications can be made within the spirit and scope of the present invention.

[0029] In the present specification, when “to” is used for a numerical range, the numerical values ​​at both ends are respectively an upper limit and a lower limit, and are included in the numerical range.

[0030] <Binder Bitumen>

[0031] The binder pitch of one embodiment has a softening point of 70°C to 120°C, a fixed carbon content of 50.0% by mass or more, a quinoline insoluble content of 18.0% by mass or less, an initial distillation point of 320°C or more, and a Casson yield value at a softening point + 100°C of 0.18 Pa or more. The softening point, fixed carbon content, quinoline insoluble content, initial distillation point, and Casson yield value can be measured by the method described in the Examples.

[0032] The softening point of the binder asphalt in one embodiment is 70°C or more, preferably 80°C or more, and more preferably 85°C or more. The softening point of the binder asphalt in one embodiment is 120°C or less, preferably 110°C or less, and more preferably 100°C or less. These upper and lower limits may be combined arbitrarily. If the softening point is in the above temperature range, the binder asphalt is sufficiently softened at the kneading temperature (e.g., 130°C to 170°C) and exhibits good kneading properties, which is therefore preferred.

[0033] There is a tendency that the higher the fixed carbon content, the higher the carbonization rate, and as a result, there is a tendency that the density of the obtained carbon material becomes higher. The fixed carbon content of the binder pitch of one embodiment is 50.0 mass% or more, and more preferably 51.0 mass% or more. The upper limit of the fixed carbon content is not particularly limited, and is, for example, 75.0 mass% or 85.0 mass%.

[0034] The quinoline insoluble component (QI) of the binder asphalt of one embodiment is 18.0 mass % or less, preferably 15.0 mass % or less, and more preferably 10.0 mass % or less. It should be noted that the quinoline insoluble component of the binder asphalt includes, in addition to the quinoline insoluble component contained in the base asphalt, carbon powder added to the base asphalt. The carbon powder can be added, for example, in step 3 described later. The component detected as the quinoline insoluble component (QI) is preferably substantially free of intermediate phase spherulites that are produced during the heat treatment of petroleum-based heavy oil. As long as the Casson yield value of the binder asphalt at the softening point + 100°C is 0.18 Pa or more, the lower limit of the quinoline insoluble component is not particularly limited, for example, 1.0 mass % or 1.5 mass %.

[0035] The initial boiling point of the binder asphalt of one embodiment is 320°C or higher, preferably 340°C or higher. If the initial boiling point is 320°C or higher, the amount of light components volatilized at the kneading temperature (e.g., 130°C to 170°C) is small, so the viscosity of the asphalt is unlikely to increase during kneading, and kneading can be performed well. As long as the softening point of the binder asphalt is in the range of 70°C to 120°C, the upper limit of the initial boiling point is not particularly limited, and is, for example, 400°C or 450°C.

[0036] The Casson yield value of the binder pitch at the softening point + 100°C of one embodiment is 0.18 Pa or more, more preferably 0.20 Pa or more, and even more preferably 0.22 Pa or more. The so-called "softening point of the binder pitch at + 100°C" means, for example, that the temperature for measuring the yield value is set to 193°C when the softening point of the binder pitch is 93°C. If the Casson yield value at the softening point + 100°C is 0.18 Pa or more, the loss of the binder pitch from the molded body that may occur during firing can be suppressed, and there is a tendency for the carbonization rate to increase, so it is preferred. The upper limit of the Casson yield value at the softening point + 100°C is not particularly limited, and is, for example, 1.5 Pa or 1.0 Pa.

[0037] The Casson yield value can be calculated by measuring the relationship between the shear rate and the shear stress at the measuring temperature according to the method described in ASTM D5018-18, and applying the Casson formula (1) to the curve obtained by plotting the two measured values. That is, if S is the shear stress (Pa), D is the shear rate (s -1 ), τ0: Casson yield value (Pa), μ0: Casson viscosity (Pa·s), then the Casson yield value can be used as the S of the Casson formula (1) 1 / 2 Relative to D 1 / 2 The y-intercept of the graph (τ0 1 / 2 ) is calculated by squaring the value.

[0038] S 1 / 2 =τ0 1 / 2 +μ0 1 / 2 ·D 1 / 2 (1)

[0039] <Method for producing binder pitch for carbon material production>

[0040] The method for producing the binder pitch for carbon material production is not particularly limited as long as it is a method that can obtain a binder pitch that satisfies the specified physical property values, and examples thereof include the following production methods. The method for producing the binder pitch for carbon material production according to one embodiment includes at least the following steps 1 to 3 in order, and other steps may be added.

[0041] Step 1 (heat treatment step): a step of heat treating petroleum-based heavy oil

[0042] Step 2 (distillation step): distilling the heat-treated product obtained in step 1 to obtain a base asphalt having a softening point of 60°C to 110°C, a fixed carbon content of 49.0% by mass or more, an initial distillation point of 320°C or more, and a quinoline insoluble component (QI) of 1.0% by mass or less as a high boiling point component.

[0043] Step 3 (carbon powder mixing step): a step of adding carbon powder to the base asphalt obtained in step 2 and mixing to obtain a binder asphalt.

[0044] The petroleum-based heavy oil used as a raw material is not particularly limited as long as it can obtain a base asphalt with desired properties in step 2, but preferably has the following composition. That is, the content of the fraction with a boiling point below 150°C in the petroleum-based heavy oil is preferably 5% by mass or less, more preferably 2% by mass or less, and further preferably 1% by mass or less. The content of the fraction with a boiling point of 150°C or more and less than 450°C in the petroleum-based heavy oil is preferably 75% by mass or more, more preferably 85% by mass or more, and further preferably 90% by mass or more. The content of the fraction with a boiling point of 450°C or more and less than 550°C in the petroleum-based heavy oil is preferably 15% by mass or less, more preferably 10% by mass or less, and further preferably 8% by mass or less. The content of the fraction with a boiling point of 550°C or more in the petroleum-based heavy oil is preferably 5% by mass or less, preferably 3% by mass or less, and further preferably 1% by mass or less. The content of the fraction in each temperature range described here refers to the distillate amount in each temperature range when the distillation curve of the petroleum-based heavy oil is obtained. The calculation method of the distillation curve can be determined by selecting an appropriate method from JIS K2254:2018, ASTM D7500-15, and ASTM D7169-16 according to the type of the petroleum-based heavy oil.

[0045] As a petroleum-based heavy oil having the above composition, ethylene tar light components can be exemplified. In the petrochemical industry, naphtha and the like are usually thermally decomposed at high temperatures, and the resulting thermal decomposition products are distilled to separate into fractions such as ethylene, propylene and other olefins, aromatic compounds such as benzene, toluene, and xylene, pyrolysis gasoline, and pyrolysis kerosene to produce products. The heavy fraction with the highest boiling point among these fractions is called ethylene tar, which is used as a raw material and fuel for carbon black and the like (see Figure 1 ). Many thermal decomposition facilities for naphtha and the like are called ethylene facilities, and therefore the above-mentioned heavy fraction is called ethylene tar.

[0046] The properties of ethylene tar obtained by thermal decomposition of a raw material containing naphtha vary depending on the type of raw material containing naphtha, thermal decomposition conditions, operating conditions of a purification distillation column, etc., but generally, the 50% distillation temperature is 200°C to 400°C, the content of aromatic carbon is 50% by mass or more, the flash point is 70°C to 100°C, and the dynamic viscosity at 50°C is less than 40 mm. 2 / s. However, ethylene tar is a mixture of hydrocarbons, so the above value may vary slightly.

[0047] The so-called ethylene tar light component refers to a distillate obtained by distilling and removing any proportion (e.g., 5% to 70% by mass) of light components from ethylene tar by distillation operation or the like. The high boiling point component obtained at this time is called ethylene tar heavy component. As long as it falls within the range of the above-mentioned preferred composition, ethylene tar, ethylene tar heavy components, and other heavy oils can be added to the ethylene tar light component. As other heavy oils, there are no particular restrictions, and examples thereof include fluidized contact cracking oil (FCC clarified oil), atmospheric distillation residual oil, vacuum distillation residual oil, heavy oil obtained by hydrogenating various petroleum-based heavy oils, cracked kerosene, coal tar, etc. The sulfur and nitrogen components in asphalt become the cause of puffing during calcination, so they are preferably less. In the case of using asphalt containing a large amount of metal components to manufacture graphite electrodes, these metal components evaporate during graphitization, and the density of the graphite electrode decreases, so sometimes the quality of the product is not ideal. From these viewpoints, as other heavy oils, heavy oils with low sulfur, nitrogen and metal components are preferred. As such other heavy oils, fluidized contact cracking oil (FCC clarified oil) and cracked kerosene are preferred. The properties of fluidized contact cracking oil (FCC clarified oil) depend on the raw materials, operating conditions, etc., but generally, the 50% distillation temperature is 300°C to 450°C, the flash point is 60°C to 160°C, and the dynamic viscosity at 40°C is less than 40 mm. 2 / s. However, since fluid contact cracking oil (FCC clarified oil) is a complex mixture, the above-mentioned value may vary slightly. In one embodiment, the petroleum-based heavy oil is an ethylene tar light component.

[0048] Pyrolysis kerosene is a mixture of hydrocarbons with carbon atoms of 9 or more produced by petrochemical processes, and is a fraction having a boiling point in the range of 90°C to 230°C at 1 atmosphere. However, since pyrolysis kerosene is a mixture of hydrocarbons, the carbon number and boiling point may vary slightly.

[0049] Examples of the main components of the cracked kerosene include xylene, styrene, allylbenzene, propylbenzene, methylethylbenzene, trimethylbenzene, methylstyrene, dicyclopentadiene, indane, indene, methylpropylbenzene, methylpropylenebenzene, ethylstyrene, divinylbenzene, methylindene, naphthalene, and methyldicyclopentadiene.

[0050] (Process 1: Heat treatment process)

[0051] Step 1 is a step of heat treating the petroleum-based heavy oil. The heat treatment is preferably carried out in a closed container in a non-oxidizing gas atmosphere. Examples of the non-oxidizing gas include nitrogen, argon, hydrogen, methane, ethane and other lower alkanes and mixed gases of these non-oxidizing gases. From the perspective of cost and ease of operation, nitrogen is preferred.

[0052] The heat treatment temperature is preferably 380°C or more, more preferably 400°C or more, and further preferably 410°C or more. The heat treatment temperature is preferably 500°C or less, more preferably 480°C or less, and further preferably 450°C or less. These upper and lower limits may be combined arbitrarily. The preferred range is 380°C to 500°C, more preferably 400°C to 480°C, and further preferably 410°C to 450°C.

[0053] The appropriate heat treatment time varies according to the heat treatment temperature. When the heat treatment temperature is 380°C to 400°C, it is preferably 8 hours to 48 hours, and more preferably 16 to 48 hours, starting from the time when the specified heat treatment temperature is reached (the same below). When the heat treatment temperature is higher than 400°C and below 430°C, it is preferably 1 hour to 24 hours, and more preferably 3 hours to 16 hours. When the heat treatment temperature is higher than 430°C and below 500°C, it is preferably 0.1 hours to 16 hours, and more preferably 0.5 hours to 8 hours. The upper limit and lower limit of the appropriate heat treatment time under each heat treatment temperature condition can be arbitrarily combined.

[0054] The pressure at the beginning of the heat treatment (initial pressure) is preferably 0 MPaG, but there is no particular limitation. The pressure in the closed container increases due to the hydrogen and lower alkanes such as methane and ethane produced by the thermal decomposition during the heat treatment. There is no limit to the pressure in the closed container, and it can be depressurized as needed. However, when implemented under pressurized conditions, there is a tendency for the yield of the base asphalt obtained in step 2 to increase, so it is preferred. As a preferred pressure range when implemented under pressurized conditions, for example, it is about 0.1 MPaG to 15 MPaG.

[0055] As described in Japanese Patent Application Laid-Open Nos. 60-179493 and 60-240790, a solid catalyst or the like may be added during the heat treatment. However, in this case, a step of removing the solid catalyst must be added before step 3.

[0056] (Step 2: Distillation Step)

[0057] Step 2 is a step in which the heat-treated product obtained in step 1 is distilled to remove low-boiling substances and obtain asphalt (base asphalt) having desired characteristics as a high-boiling component. The distillation method in step 2 may be any method of atmospheric distillation, vacuum distillation (vacuum distillation) or a method combining atmospheric distillation and vacuum distillation, and can be appropriately selected. The internal temperature of the distillation apparatus is preferably not more than 360°C. This is because if it exceeds 360°C, polymerization and other reactions are likely to occur, and sometimes coking occurs on the inner wall of the distillation apparatus. Although the lower limit temperature does not affect the characteristics of the asphalt, if the temperature is low, the distillation pressure must be reduced to distill off the low-boiling substances. Therefore, from the perspective of economic efficiency, it is preferably 200°C or more. In the case of vacuum distillation (vacuum distillation), in order to obtain a base asphalt with an initial boiling point of 320°C or more, the pressure during distillation is preferably 100PaA to 10000PaA, more preferably 500PaA to 3000PaA, and even more preferably 800PaA to 2000PaA. Generally, the higher the distillation end point, the higher the initial boiling point. Although it also depends on the type of petroleum-based heavy oil used, the heat treatment conditions of step 1 and the distillation conditions of step 2, in order to make the initial boiling point of the obtained base asphalt above 320°C, the distillation end point when converted to normal pressure is preferably above 320°C, and more preferably above 330°C.

[0058] The softening point of the base asphalt of one embodiment obtained in step 2 is preferably above 60°C, and more preferably above 65°C. The softening point of the base asphalt of one embodiment obtained in step 2 is preferably below 110°C, and more preferably below 100°C. These upper and lower limits can be combined arbitrarily. The preferred range is 60°C to 110°C, and more preferably 65°C to 100°C. Although it also depends on the type and amount of carbon powder added and mixed in step 3, if the softening point is 60°C to 110°C, the softening point of the obtained adhesive asphalt is 70°C to 120°C, so it is preferred. The softening point is determined by the method described in the example item.

[0059] The fixed carbon content of the base asphalt of one embodiment obtained in step 2 is preferably 49.0% by mass or more, and more preferably 50.0% by mass or more. Although it also depends on the type and amount of carbon powder added and mixed in step 3, if the fixed carbon content is 49.0% by mass or more, the fixed carbon content of the obtained binder asphalt is 50.0% by mass or more, which is preferred. The upper limit of the fixed carbon content is not particularly limited, and is, for example, 75.0% by mass or 85.0% by mass. The fixed carbon content is determined by the method described in the Examples.

[0060] The initial distillation point of the base asphalt of one embodiment is preferably above 320°C, and more preferably above 330°C. Although it also depends on the conditions of step 3, if the initial distillation point of the base asphalt is above 320°C, the initial distillation point of the obtained binder asphalt is also above 320°C, so it is preferred. The upper limit of the initial distillation point of the base asphalt of one embodiment is not particularly limited as long as the softening point of the obtained base asphalt is 60°C to 110°C, but is preferably below 450°C, and more preferably below 400°C. These upper and lower limits can be combined arbitrarily. The preferred range is 320 to 450°C, and more preferably 330 to 400°C. The determination of the initial distillation point is carried out by the method described in the example item.

[0061] The quinoline insoluble component (QI) (mesophase spherulites) produced by heat treatment of petroleum-based heavy oil can cause a decrease in kneading properties (Light Metals 2006, 535-540.), so the quinoline insoluble component (QI) of the base asphalt of one embodiment is preferably 1.0 mass % or less, more preferably 0.5 mass % or less, and further preferably 0.1 mass % or less. The lower limit of the QI of the base asphalt is not particularly limited, for example, 0.0 mass % or 0.001 mass %. The determination of QI is carried out by the method described in the example item.

[0062] (Process 3: Carbon powder mixing process)

[0063] Step 3 is a step of adding carbon powder to the base asphalt obtained in step 2 and mixing it. The carbon powder used is not particularly limited as long as it can increase the Casson yield value of the binder asphalt without deteriorating the kneading property of the obtained binder asphalt. For example, a carbon powder with a particle size of about 1nm to 20μm can be used. Here, in the above-mentioned particle size range, the particle size of particles greater than 10nm refers to the average particle size (median particle size: D50) when measured by laser diffraction / scattering method, and the particle size of particles less than 10nm refers to the arithmetic mean particle size when measured by electron microscope observation. As such carbon powder, graphite powders such as artificial graphite powder and natural graphite powder, coke powder and free carbon powder (1st QI) in coal tar can be cited, but artificial graphite powder and coke powder are preferred. Carbon powder generated by side reactions when manufacturing graphite electrodes can also be used. Carbon powder can be used alone or as a mixture of two or more. In one embodiment, the carbon powder is artificial graphite powder.

[0064] Relative to 100 parts by mass of base asphalt, the addition amount of carbon powder is preferably 1.0 parts by mass or more, more preferably 3.0 parts by mass or more, and further preferably 5.0 parts by mass or more. Relative to 100 parts by mass of base asphalt, the addition amount of carbon powder is preferably 22.0 parts by mass or less, more preferably 18.0 parts by mass or less, and further preferably 11.0 parts by mass or less. These upper and lower limits can be combined arbitrarily. Relative to 100 parts by mass of base asphalt, the preferred range is 1.0 parts by mass or more and 22.0 parts by mass or less, more preferably 3.0 parts by mass or more and 18.0 parts by mass or less, and further preferably 5.0 parts by mass or more and 11.0 parts by mass or less. Although it also depends on the amount of quinoline insoluble components in the base asphalt, if it is the above-mentioned range, the quinoline insoluble components in the obtained adhesive asphalt are 18.0% by mass or less, which can improve the Casson yield value without deteriorating the kneading property, and therefore, can improve the carbonization rate.

[0065] The method for mixing the base asphalt and the carbon powder is not particularly limited, but a method in which the carbon powder is well dispersed in the base asphalt is preferably used.

[0066] For example, a method of mixing base asphalt with carbon powder at a temperature above the softening point of the base asphalt can be cited. When the base asphalt and carbon powder are mixed at a temperature above the softening point of the base asphalt, the mixing temperature is preferably below 350°C, more preferably below 250°C, and further preferably below 200°C. Although it also depends on the mixing conditions, if it is below 350°C, the deterioration of the base asphalt that may occur during mixing can be suppressed to a minimum. The mixing time is not particularly limited, for example, 5 minutes to 24 hours. Although it also depends on the mixing conditions, if it is within the above range, the carbon powder can be well dispersed in the base asphalt. The mixing atmosphere is not particularly limited, and can be carried out under air or in a non-oxidizing gas atmosphere. From the perspective of suppressing the deterioration of the base asphalt that may occur during mixing to a minimum, it is preferably implemented in a non-oxidizing gas atmosphere. As non-oxidizing gases, for example, gases of lower alkanes such as nitrogen, argon, hydrogen, methane, and ethane and mixed gases of these non-oxidizing gases can be cited. Among them, nitrogen is preferred from the viewpoint of cost and ease of handling. The apparatus for mixing is not particularly limited, and for example, a heatable mixer, kneader, etc. can be used.

[0067] As an example of other mixing methods, a method of dissolving the base asphalt in a suitable solvent and mixing it with carbon powder can be cited. In this case, a process of removing the solvent by vacuum distillation or the like is required after mixing. As a suitable solvent, there is no particular limitation as long as it is a solvent that can dissolve the base asphalt well, but it is preferably benzene, toluene, xylene, quinoline, pyridine and a mixture thereof. It is also possible to use a fraction containing more benzene and toluene obtained by a petrochemical process. As an example of such a fraction, pyrolysis gasoline and pyrolysis kerosene can be cited.

[0068] Pyrolysis gasoline is a mixture of hydrocarbons with 6 to 8 carbon atoms produced by petrochemical processes, and is a fraction with a boiling point in the range of 65°C to 150°C at 1 atmosphere. However, since pyrolysis gasoline is a mixture of hydrocarbons, the number of carbon atoms and boiling point may vary slightly.

[0069] Examples of the main components of pyrolysis gasoline include benzene, toluene, ethylbenzene, xylene, styrene, hexane and the like.

[0070] Regarding cracked kerosene, it is as mentioned above.

[0071] Mixing using a solvent can be carried out at room temperature or under heating conditions. When mixing is carried out under normal pressure, the mixing is preferably carried out below the boiling point of the solvent used. When mixing is carried out at a temperature above the boiling point of the solvent used, it can be carried out under reflux conditions or under pressure using a closed container. Although it also depends on the mixing conditions, the mixing temperature is preferably below 350°C, more preferably below 250°C, and further preferably below 200°C. Although it also depends on the mixing conditions, if it is below 350°C, the deterioration of the base asphalt that may occur during mixing can be suppressed to a minimum. The mixing time is not particularly limited, for example, 5 minutes to 24 hours. Although it also depends on the mixing conditions, if it is within the above range, the carbon powder can be well dispersed in the base asphalt. The mixing atmosphere is not particularly limited, and can be carried out under air or in a non-oxidizing gas atmosphere. From the perspective of suppressing the deterioration of the base asphalt that may occur during mixing to a minimum, it is preferably carried out in a non-oxidizing gas atmosphere. Examples of the non-oxidizing gas include nitrogen, argon, hydrogen, lower alkanes such as methane and ethane, and mixed gases of these non-oxidizing gases. Among these, nitrogen is preferred from the viewpoint of cost and ease of handling.

[0072] When the base asphalt and the carbon powder are mixed using a solvent, a solvent removal step is required after step 3. The method for removing the solvent is not particularly limited, but it is preferably a method that can efficiently remove the solvent without deteriorating the base asphalt. As such a solvent removal method, distillation and the like can be cited. The distillation method in this case can be any method of atmospheric distillation, reduced pressure distillation (vacuum distillation) or a method combining atmospheric distillation and reduced pressure distillation, and can be appropriately selected. The internal temperature of the distillation apparatus is preferably not more than 360°C. This is because, if it exceeds 360°C, reactions such as polymerization are likely to occur, and sometimes the base asphalt will deteriorate. The lower limit temperature and the pressure when performing reduced pressure distillation (vacuum distillation) will not affect the physical properties of the base asphalt, so the conditions can be appropriately selected according to the type of solvent used.

[0073] <Method for producing carbon material>

[0074] In a method for manufacturing a carbon material according to one embodiment, as a binder pitch, a pitch having a softening point of 70°C to 120°C, a fixed carbon content of 50.0% by mass or more, a quinoline insoluble component of 18.0% by mass or less, an initial distillation point of 320°C or more, and a Casson yield value of 0.18 Pa or more at a softening point of +100°C is used. The so-called carbon material refers to various shaped carbon materials such as graphite tubes, graphite crucibles, graphite boats, and graphite electrodes. The manufacturing process of the exemplified carbon material such as the graphite electrode is described below.

[0075] 1. Mixing process

[0076] The process of mixing and kneading needle coke and binder pitch together

[0077] 2. Molding process

[0078] The process of molding the kneaded product to obtain a molded body of a predetermined size and shape

[0079] 3. Firing process

[0080] Step of firing the molded body to obtain a fired body

[0081] 4. Impregnation process

[0082] Step of filling and impregnating the fired body with asphalt

[0083] 5. Re-firing process

[0084] Step of again firing the fired body filled with impregnated asphalt to obtain a re-fired body

[0085] 6. Graphitization process

[0086] Step of graphitizing the re-fired body to obtain a graphitized body

[0087] 7. Processing procedures

[0088] The process of forming a graphite body into a predetermined shape by cutting or the like to produce a carbon material such as a graphite electrode

[0089] 1. Mixing process

[0090] The needle coke that has been crushed, classified, and mixed in a predetermined proportion is mixed and kneaded with a binder pitch. The amount of the binder pitch varies depending on the mixing method and the molding method, but is generally about 20 to 30 parts by mass per 100 parts by mass of the needle coke.

[0091] The kneaded material may contain a flatulence inhibitor such as iron oxide.

[0092] For mixing and kneading, a commercially available mixer or kneading machine can be used. Specific examples include mixers and kneading machines such as mixers and kneaders. The kneading temperature varies depending on the binder asphalt used, but is generally about 130° C. to 170° C. After kneading, the kneaded product is cooled to a temperature suitable for subsequent molding (e.g., 100° C. to 130° C.).

[0093] In this step, as a binder asphalt, a asphalt having a softening point of 70°C to 120°C, a fixed carbon content of 50.0 mass % or more, a quinoline insoluble component of 18.0 mass % or less, an initial boiling point of 320°C or more, and a Casson yield value of 0.18 Pa or more at a softening point of +100°C is used. The details of the asphalt are as described above.

[0094] 2. Molding process

[0095] The kneaded product is molded to obtain a molded body of a predetermined size and shape. The molding method can be appropriately selected from extrusion molding, die molding, etc. according to the target carbon material. When the target carbon material is a graphite electrode, it is usually extruded into a cylindrical shape.

[0096] 3. Firing process

[0097] The molded body of the previous step is heated and fired at 700°C to 1000°C to obtain a fired body. The firing process is preferably carried out in a non-oxidizing atmosphere of combustion exhaust gas. The molded body softens at the initial stage of heating, and a large amount of decomposition gas is generated by thermal decomposition and polycondensation of the binder pitch at 200°C to 500°C, resulting in the formation of pores and volume shrinkage. At 500°C to 600°C, the binder pitch is carbonized. The firing process, including cooling, usually takes about 1 month.

[0098] 4. Impregnation process

[0099] In the firing process, generally, 35% to 45% of the mass of the binder asphalt is lost as volatile components. At this time, a large number of pores are generated in the fired body. The process of filling the pores with impregnation asphalt is the impregnation process. The impregnation can be performed, for example, as follows: the fired body is placed in an autoclave, and after degassing under reduced pressure, the molten impregnation asphalt is injected, and the impregnation asphalt is injected into the pores at about 200°C using a gas pressure of about 1 MPa.

[0100] Although it varies depending on the type of carbon material to be produced and the production method, etc., the softening point of the impregnated pitch used is preferably 80° C. to 120° C. The fixed carbon content is preferably 45.0% by mass or more, and more preferably 50.0% by mass or more.

[0101] 5. Re-firing process

[0102] The fired body filled with the impregnated pitch is fired again to obtain a re-fired body. The re-fire can also be performed under the same conditions as the above-mentioned firing step. The impregnation step and the re-fire step can be repeated as needed.

[0103] 6. Graphitization process

[0104] The reburned body is placed in a furnace surrounded by insulating materials (Acheson furnace, LWG furnace, etc.), and the packing coke or the reburned body is heated by resistance heating by power supply, and the reburned body is heat treated. The graphitization temperature is 2000°C to 3000°C. This temperature is necessary to convert the amorphous carbon in the reburned body into crystalline graphite. In order to convert the reburned body into a graphitized body, it is preferred to perform heat treatment for several days.

[0105] 7. Processing procedures

[0106] The graphitized body is made into a carbon material of a predetermined shape, such as a graphite electrode product, by mechanical processing such as cutting. The density (bulk density) of the graphite electrode varies depending on the electric furnace equipment used and the operating conditions of the electric furnace, but is preferably 1.5 g / cm 3 ~1.9g / cm 3 .

[0107] Example

[0108] The present invention will be further described with reference to the following Examples and Comparative Examples. However, these Examples are merely examples of the present invention, and the present invention is not limited to these Examples.

[0109] <Measurement method of softening point (SP)>

[0110] The softening point is measured in accordance with "8. Softening point determination method of tar pitch (ring and ball method)" of JIS K 2425:2006 "Testing methods for creosote, processed tar and tar pitch".

[0111] <Method for measuring fixed carbon content>

[0112] The fixed carbon content is measured in accordance with "11. Fixed carbon content method" of JIS K 2425:2006 "Testing methods for creosote, processed tar and tar pitch".

[0113] <Method for Determination of Quinoline Insoluble Component (QI)>

[0114] The quinoline insoluble content (QI) is measured by the filtration method described in "15. Quantitative determination of quinoline insoluble content of tar pitch" of JIS K 2425:2006 "Testing methods for creosote, processed tar, and tar pitch".

[0115] <Method for determining initial boiling point>

[0116] The initial distillation point of asphalt is measured in accordance with "6. Vacuum method" described in JIS K 2254:2018 "Petroleum products-Determination of distillation properties".

[0117] <Method for measuring Casson yield value>

[0118] The relationship between shear rate and shear stress at various temperatures was measured according to the method described in ASTM D5018-18. In the measurement, the shear rate was changed so that the torque was in the range of 10% to 90%, and the viscosity at each shear rate was recorded. As an example of the measurement result, Figure 3 The measurement results of Example 1 are shown in FIG. Based on the measured data, the yield value is calculated using the Casson formula (1). As an example of calculating the yield value, Figure 4 Casson curve of Example 1 is shown in FIG. The apparatus used for the measurement is as follows.

[0119] Rotational viscometer (Brookfield, DV-II+Pro)

[0120] Constant temperature metal bath (ThermoCell) (Brookfield, HT-110115ADP)

[0121] Main axis (Brookfield, SC4-21)

[0122] Chamber (Brookfield Corporation, HT-2DB-100)

[0123] <Method for measuring true density of asphalt>

[0124] The true density of the pitch was measured by a constant volume expansion method using an Acupic II 1340 (Micromeritics). The measurement was performed at 25°C using helium as a replacement gas.

[0125] <Electrode Evaluation>

[0126] Using a laboratory kneader (Toshino Co., Ltd., TDR200-3), binder pitch and needle coke were mixed (needle coke: binder pitch = 8:2, mass ratio), and molded into the shape of an electrode sheet (cylindrical; 50mmΦ×35mm) by die molding to obtain a molded body. The molded body was sintered at about 1000°C to obtain a sintered body. The density of the molded body and the sintered body was measured in accordance with JIS R 7222:2017 "Methods for determination of physical properties of graphite raw materials 7. Method for determination of bulk density". The carbonization rate was calculated using formula (2).

[0127]

[0128] W1: Quality of the binder bitumen used to make the molded body

[0129] W2: The quality of needle coke used to make molded bodies

[0130] W3: sintered body mass

[0131] <Toner>

[0132] Artificial graphite powder (UF-G5) (Rezonak Co., Ltd., particle size: 3 μm) was used as the artificial graphite powder, and carbon black (MA230) (Mitsubishi Chemical Co., Ltd., particle size: 30 nm) was used as the carbon black powder.

[0133] <Evaluation of stability at mixing temperature>

[0134] The binder pitch and needle coke of the examples and comparative examples were mixed at 150°C for 5 minutes (needle coke: binder pitch = 3:7, mass ratio), and the prepared paste was used as a measurement sample for evaluation. -1The measured sample was measured for 1 hour under the conditions of , and the change in viscosity over time was recorded. MCR72 (Anton Paar) was used for the viscosity measurement. The viscosity 10 minutes after the start of the measurement was used as a reference, and the viscosity increase rate (%) was calculated using formula (3). If the viscosity increase rate 60 minutes after the start of the measurement is 1.0% or less, it is judged to be stable at the kneading temperature (here 170°C). When the viscosity increase rate 60 minutes after the start of the measurement is 1.0% or less, it is judged to be "good", and when the viscosity increase rate is greater than 1.0%, it is judged to be "poor", and the results are summarized in Table 1. The change in viscosity increase rate over time is recorded in Figure 2 middle.

[0135]

[0136] η 10min : Viscosity 10 minutes after the start of measurement

[0137] η Xmin : Viscosity after measurement starts X minutes later

[0138] <Heavy and light components of ethylene tar>

[0139] 894 kg of ethylene tar (5% by mass distillation temperature: 196°C, 90% by mass distillation temperature: 575°C) was used as a raw material, and distilled and purified using a distillation apparatus having 15 theoretical plates (Suzel packing) at a kettle temperature of 101°C and an operating pressure of 533-1067 PaA to obtain 544 kg of ethylene tar heavy components as kettle residue. The initial boiling point of the obtained ethylene tar heavy components was 218°C. The components obtained as distilled components were used as ethylene tar light components.

[0140] <Method for Determining Raw Material Composition (Boiling Point Range)>

[0141] The raw material composition (boiling point range) of the raw material ethylene tar and the ethylene tar light component was measured according to the method described in ASTM D7500-15 "Standard Test Method for Determination of Boiling Range Distribution of Distillates and Lubricating Base Oils-in Boiling Range from 100°C to 735°C by Gas Chromatography". AC SIMDIS Analyzer (PAC) was used for the measurement.

[0142] (Example 1)

[0143] 3000 g of ethylene tar light component was introduced into a SUS autoclave with a capacity of 6.0 L. The autoclave was sealed in a nitrogen atmosphere, and the temperature inside the container was raised to 430°C at a rate of 4°C / min while stirring, and heat treatment was carried out. After 6 hours after reaching 430°C, it was left to cool to room temperature and the heat-treated product was taken out. The heat-treated product was subjected to vacuum distillation using a vacuum distillation apparatus to distill off the low-boiling point components, and 720 g of base asphalt A (yield 24%) was obtained as a high-boiling point component. The obtained base asphalt A: 110.4 g and artificial graphite powder: 9.6 g were placed in a metal beaker, heated to 140°C in an oil bath, and heated and mixed for 30 minutes using a Three-One Motor, thereby preparing 120 g of adhesive asphalt, and various evaluations were carried out.

[0144] (Comparative Example 1)

[0145] Various evaluations were carried out using the base asphalt A obtained in Example 1 as a binder asphalt.

[0146] (Comparative Example 2)

[0147] 114 g of the base asphalt A obtained in Example 1 and 6 g of carbon black powder were placed in a metal beaker, heated to 140° C. in an oil bath, and heated and mixed for 30 minutes using a Three-One Motor to prepare 120 g of a binder asphalt, which was then subjected to various evaluations.

[0148] (Comparative Example 3)

[0149] 550 g of ethylene tar (5% by mass distillation temperature: 196°C, 90% by mass distillation temperature: 575°C) was introduced into a 1.0 L SUS autoclave. The autoclave was sealed in a nitrogen atmosphere, and the temperature inside the container was raised to 380°C at a rate of 4°C / min while stirring, and heat treatment was carried out. After 36 hours after reaching 380°C, the product was cooled to room temperature and the heat-treated product was taken out. The heat-treated product was subjected to vacuum distillation using a vacuum distillation apparatus to distill off the low-boiling point components, and 226 g of base asphalt B (yield 41%) was obtained as a high-boiling point component. The obtained base asphalt B: 110.4 g and artificial graphite powder: 9.6 g were placed in a metal beaker, heated to 140°C in an oil bath, and heated and mixed for 30 minutes using a Three-One Motor, thereby preparing 120 g of adhesive asphalt, and various evaluations were carried out.

[0150] [Table 1-1]

[0151]

[0152] [Table 1-2]

[0153]

[0154] When comparing the embodiments and comparative examples, it can be seen that when a binder pitch having a Casson yield value of 0.18 Pa or more is used even if the softening point and the fixed carbon content are the same, a very high carbonization rate can be obtained. It is believed that one reason for this is that the loss of the binder pitch from the molded body during firing is suppressed as described above. In Comparative Example 3, since the Casson yield value is above 0.18 Pa, there is a tendency for the carbonization rate to increase, but the initial distillation point is low, and the viscosity increases during mixing. Therefore, the mixing property decreases, there is a tendency for the density of the molded body to decrease, and thus there is a tendency for the density of the fired body to decrease. From the above, it can be confirmed that in order to obtain a higher density carbon material, it is effective to use a binder pitch having an appropriate softening point, fixed carbon content, quinoline insoluble component, initial distillation point and Casson yield value at a softening point + 100°C.

Claims

1. A binder pitch for carbon material manufacturing, having a softening point of 70°C to 120°C, a fixed carbon content of 50.0% by mass or more, a quinoline insoluble component of 18.0% by mass or less, an initial distillation point of 320°C or more, and a Casson yield value of 0.18 Pa or more at a softening point of +100°C. 2 . The binder pitch for producing a carbon material according to claim 1 , wherein the carbon material is a graphite electrode.

3. A method for producing a carbon material, wherein: As the binder asphalt, use is made of asphalt having a softening point of 70°C to 120°C, a fixed carbon content of 50.0 mass % or more, a quinoline insoluble component of 18.0 mass % or less, an initial boiling point of 320°C or more, and a Casson yield value of 0.18 Pa or more at a softening point + 100°C. The method for producing a carbon material according to claim 3 , wherein the carbon material is a graphite electrode.

Citation Information

Patent Citations

  • Treatment of ethylene heavy end

    JP1985179493A

  • Method for treating ethylene heavy end

    JP1985240790A

  • High coking value pitch

    US6352637B1